Penguatan promosi pariwisata Desa Wisata Kandri melalui pelatihan pembuatan booklet informatif - Naila Rohmah; Alfin Rosyidha; Nabyla Rizky Putri Handayani; Assita Hilda Putri Assiva (Tintamas: Jurnal Pengabdian Indonesia Emas, 2026)
This community service project aimed to improve the capacity of Kandri Tourism Village residents in promoting local potential through digital booklet design training using Canva. The program was initiated in response to the limited quality of visual promotional materials and the lack of access to design training in the village. The training was delivered using a participatory and collaborative approach, covering needs assessment, technical training, content development, booklet production, and evaluation. The results indicated a notable improvement in participants' ability to structure promotional narratives, apply basic visual design principles, and independently use Canva for media creation. Moreover, the training enhanced community confidence in presenting Kandri’s tourism attractions in a more informative and engaging format. This program demonstrates that simple, digital-based training can serve as an effective strategy to strengthen community involvement in tourism village promotion